Качеством управляет ЭВМ - Артемьев В. Н. Вячеслав Николаевич; Гродинский П. Г. Павел Григорьевич; Карпов В. В. Валерий Владимирович; Кузнецов А. В. Алексей Васильевич (Москва, Московский рабочий, 1979)
Исключено из фонда НТБ ТПУ